The impact of technological adoption and financial literacy on international entrepreneur intention among youth: the case of agriculture sector / Mohamad Syahril Iman Mohamad Faisal - Mohamad Faisal, Mohamad Syahril Iman (2023)
Due to its significance to the growth of many nations, entrepreneurship intention study has been and will continue to be a topic of interest to scholars. Many topics have been covered in the literature on entrepreneurial intention, with a lot of attention paid to the variables that affect entrepreneurial intention. Yet, the majority of these investigations were carried out elsewhere. The study chose the agriculture sector since it is a sector that this topic always focuses on when identifying entrepreneurial intention. This study looks at Malaysian youth's intentions to become international entrepreneurs. It specifically seeks to ascertain the impact of technological adoption on young people's intentions to become international entrepreneurs and the relationship between each aspect of financial literacy (financial attitude, financial behaviour, and financial knowledge) and technological adoption. Data analysis using partial least squares structural equation modelling was done. In this study, purposive data sampling was performed. The PLS-SEM analysis results demonstrated that financial literacy (financial attitude, financial behaviour and financial knowledge) and technological adoption have a favourable impact on young people's intention to become international entrepreneurs. The findings of this study showed that technological adoption moderated the relationship between youth international entrepreneur intention and financial literacy (financial attitude, financial behaviour, and financial knowledge). The results of this study add to the body of information and aid in the development of policies and programmes by the executive branch and other decision-makers. This research can also be used by any young person who wants to start their own business in Malaysia's agriculture sector.